Enhancing oxidative stability of tocopherol‐enriched edible oils using short‐term exposure to microwave irradiation. Issue 12 (18th November 2021) - Choi, Hyuk; Na, HeeSun; Kim, SungHwa; Lee, YoonHee; Lee, JaeHwan
Abstract: The effect of microwave irradiation on the oxidative stability of tocopherol‐enriched corn oil at temperatures of 60 or 100°C was evaluated using the Rancimat assay. Short durations of microwave treatment (1 min) on 10‐g oil aliquots were found to increase the induction period of corn oil samples containing 500 and 1000 ppm tocopherol by 7.7% and 9.9%, respectively compared to control oils. The moisture content of tocopherol‐enriched corn oil decreased by 15% compared to that of corn oil after 1 min of microwave treatment. At 100°C, 1000 ppm tocopherol‐enriched corn oil received 3 min of microwave treatment had 5.8% and 9.9% lower primary and secondary oxidation products than control groups, respectively while this effect was not clearly observed for oils stored at 60°C. However, 15 min of microwave irradiation accelerated the rates of lipid oxidation in corn oils irrespective of the addition of tocopherol. Content of α‐ and γ‐tocopherols in 1 min of microwave irradiated samples remained more by 28.8 and 5.8%, respectively than those of controls after 9 h heat treatment at 100°C. Overall, microwave irradiation within 3 min can increase the oxidative stability of 10 g‐corn oils, especially at 100°C, which could be due to the reduced moisture content in the bulk oil matrix. Practical Application : A microwave oven is an irreplaceable home appliance and is widely used in households. Short time exposure to microwave irradiation can remove moisture efficiently from edible oils without the formation of oxidation products, which could increase the oxidative stability of these oils, especially under frying conditions. The results of this study can be utilized to ensure a longer shelf‐life of fried products in the food industry by short time treatment of microwave irradiation.